2007
DOI: 10.1007/s10863-007-9086-x
|View full text |Cite
|
Sign up to set email alerts
|

The Warburg effect and its cancer therapeutic implications

Abstract: Increased aerobic glycolysis in cancer, a phenomenon known as the Warburg effect, has been observed in various tumor cells and represents a major biochemical alteration associated with malignant transformation. Although the exact molecular mechanisms underlying this metabolic change remain to be elucidated, the profound biochemical alteration in cancer cell energy metabolism provides exciting opportunities for the development of therapeutic strategies to preferentially kill cancer cells by targeting the glycol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
213
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(219 citation statements)
references
References 61 publications
1
213
0
5
Order By: Relevance
“…3-BrOP is known to preferentially kill cancer cells with elevated glycolytic activity (Chen et al, 2007). These data suggested that miR-210 can trigger the metabolic switch from aerobic respiration to glycolysis.…”
Section: Hypoxia and Chemical Mimetic Regulate Mir-210mentioning
confidence: 95%
“…3-BrOP is known to preferentially kill cancer cells with elevated glycolytic activity (Chen et al, 2007). These data suggested that miR-210 can trigger the metabolic switch from aerobic respiration to glycolysis.…”
Section: Hypoxia and Chemical Mimetic Regulate Mir-210mentioning
confidence: 95%
“…In contrast, cancer cells depend mostly on glycolysis, the aerobic breakdown of glucose into the energy-storing molecule adenosine triphosphate (ATP). This altered energy dependency is known as the 'Warburg effect' and is a hallmark of cancer cells (Warburg, 1956;Kim and Dang, 2006;Chen et al, 2007;Gatenby and Gillies, 2007;DeBerardinis et al, 2008;Gillies et al, 2008;Hsu and Sabatini, 2008;Kroemer and Pouyssegur, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is characterized by increased glucose uptake and reliance on glycolysis for ATP production despite an available oxygen source (5). Aerobic glycolysis is believed to be a result of mitochondrial dysfunction which confers apoptotic resistance in cancer cells (6).…”
Section: Introductionmentioning
confidence: 99%